If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x = -26 + 6x Solving -7x = -26 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7x + -6x = -26 + 6x + -6x Combine like terms: -7x + -6x = -13x -13x = -26 + 6x + -6x Combine like terms: 6x + -6x = 0 -13x = -26 + 0 -13x = -26 Divide each side by '-13'. x = 2 Simplifying x = 2
| 2b-60=20 | | 2y^2-11y+14= | | x(-9+x)=0 | | 3x-1=-16 | | 6k=84 | | 11x-3=4-4x | | 5(x+6)=20 | | 28=-54 | | 18x-30=12x | | 63x^2-4x-35=0 | | 18-(3y-2)=2(y+2)+3y | | 3(3n-4)=4(2n-15) | | 3n-16=8n+29 | | X^2-16x+48=0 | | 4(4)(4*-2+2)= | | 4(4)(4x-2+2)= | | 9-3(5t-9)=-24 | | d^4=16d^2-48 | | 1.5s-.15=.6s+.0075 | | 4x-(xy+2)= | | 5x-4x+2=5 | | x^2+19x-10=0 | | 6x^2+19x-10=0 | | (2y+1)(3y-2)-(6y-1)(y+4)=-20y | | 8y-7y-6=8 | | 8y-7y-6=9 | | 50m-3=5m+32 | | 2x^3-14x+12=0 | | 5x+8=3-1 | | 7(n+5)+8(n+7)= | | 4r^6-9r^4=0 | | -8q=5q-104 |